Internet Gaming Disorder: Life Satisfaction, Negative Affect, Basic Psychological Needs, and Depression - Celik, Nur Demirbas; Yesilyurt, Ferahim; Celik, Birol (Kare Publishing, 2022)
Objective: The purpose of this study was to propose a model to examine the relationships between Internet Gaming Disorder (IGD), depression, life satisfaction, basic psychological need satisfaction, and negative affect. Method: A total of 339 university students participated in this study. Of the participants, 244 mentioned that they played digital games and 95 mentioned that they did not play any digital games. Of the 244 students who played digital games, 131 were females (53.7%) and 113 were males (46.3%). In the study, Personal Information Form, Internet Gaming Disorder-Short Form, Basic Psychological Need Satisfaction Scale, Negative Affect Scale, and the Satisfaction with Life Scale were used as data collection tools. Results: As a result of the structural equation model, it was found that the relationship between basic psychological needs and IGD was mediated by life satisfaction. Besides, it was concluded that negative affect mediated the relationship between IGD and depression. Conclusion: This study presented a new model to demonstrate that the satisfaction of basic psychological needs was essential for IGD because it affected life satisfaction, which could lead to depression and negative affect.
Keywords: Basic psychological needs; Depression; IGD; Life satisfaction; Negative affect